A comparison of the BURP and conventional and modified jaw thrust manoeuvres for orotracheal intubation using the Clarus Video System. (11th July 2013) - Lee, A. R.; Yang, S.; Shin, Y. H.; Kim, J. A.; Chung, I. S.; Cho, H. S.; Lee, J. J.
Summary We evaluated the effects of three airway manipulation manoeuvres: (a) conventional (single‐handed chin lift); (b) backward, upward and right‐sided pressure (BURP) manoeuvre; and (c) modified jaw thrust manoeuvre (two‐handed aided by an assistant) on laryngeal view and intubation time using the Clarus Video System in 215 patients undergoing general anaesthesia with orotracheal intubation. In the first part of this study, the laryngeal view was recorded as a modified Cormack–Lehane grade with each manoeuvre. In the second part, intubation was performed using the assigned airway manipulation. The primary outcome was the time to intubation, and the secondary outcomes were the modified Cormack–Lehane grade, the number of attempts and the overall success rate. There were significant differences in modified Cormack–Lehane grade between the three airway manipulations (p < 0.0001). Post‐hoc analysis indicated that the modified jaw thrust improved the laryngeal view compared with the conventional (p < 0.0001) and the BURP manoeuvres (p < 0.0001). The BURP worsened the laryngeal view compared with the conventional manoeuvre (p = 0.0132). The time to intubation in the modified jaw thrust group was shorter than with the conventional manoeuvre (p = 0.0004) and the BURP group (p < 0.0001). We conclude that the modified jaw thrust is the most effective manoeuvre at improving the laryngeal view and shortening intubation time with the Clarus Video System.